The influence of brand experience, brand trust, and brand awareness on e-WoM through customer satisfaction - Luthfi, Adam; Bagariang, John Mager; Kurniawati, Nia (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2025)
Digital transformation has revolutionized consumer-brand communication, making Electronic Word-of-Mouth (e-WoM) a vital component in building brand reputation in the digital age. This study examines the influence of brand experience, brand trust, and brand awareness on e-WoM, with customer satisfaction serving as a mediating variable. Using a quantitative approach, data were collected from 230 digitally active respondents in Indonesia through online questionnaires. The results, analyzed using multiple linear regression and mediation tests with SPSS, reveal that brand trust and brand awareness significantly affect both customer satisfaction and e-WoM, while brand experience shows no significant impact. Furthermore, customer satisfaction mediates the relationship between brand trust and brand awareness with e-WoM. These findings highlight that trust and awareness are key drivers of satisfaction and online advocacy, whereas brand experience alone may be insufficient without emotional connection or uniqueness. This study contributes to digital marketing literature by emphasizing the importance of fostering trust and enhancing brand visibility to strengthen customer engagement in increasingly competitive digital environments.